Intergenerational Communication and The Phenomenon of Culture Shock: A Case Study of Member Integration in The Sparko Solo Community - Diah Ayu Juliati; Rino Andreas (PERSPEKTIF, 2026)
Multigenerational communication in local communities forces individuals to adapt to differences in habits, values, and ways of interacting between generations. This study focuses on the phenomenon of culture shock in the multigenerational integration process in local sports communities, taking the Sparko Solo Community as a case study and the factors that influence the success of social integration within the community. This study uses a descriptive qualitative approach with a case study method. Informants were selected through purposive sampling based on their involvement and experience in the community. Data were obtained through interviews, participant observation, and documentation. Data analysis was carried out through data collection, reduction, presentation, and verification. The results of the study show that culture shock stems from differences in culture, values, communication styles, and participation patterns between generations. Culture shock has four stages: honeymoon, crisis, adjustment, and adaptation. The communication adaptation process, characterized by openness, empathy, and interaction intensity, can strengthen social integration.